Korelasi antara Pediatric Symptom Checklist-17 (PSC-17) dan Pediatric Quality Of Life Inventory (PedsQL) pada Anak Sekolah Dasar - Setiyawan, I Made Karma; Saputra, I Made Yullyantara; Sindhughosa, Wega Upendra; Apsari, Ni Luh Sri; Sinardja, Siska Permanasari; Mayangsari, Ayu Setyorini Mestika; Witarini, Komang Ayu (E-Jurnal Medika Udayana, 2024)
Background : Identification of psychosocial problems and quality of life of school-aged children should be routinely applied in child developmental health-related practices. The main concerns in measuring the quality of life of children with psychosocial disorders are mainly related to language development, cognitive development and the type of disorder. This has led to the identification of developmental disorders in school-aged children requiring specific tools (PSC-17 score and PedsQL score) designed for pediatric patients. The similarities or differences obtained based on these measurement tools will depend on the precise formulation of the questions as well as the assessment of the situation of the individual being evaluated. Methods : An analytic observational study using a cross-sectional design involve three elementary schools in the Jimbaran area, Badung, Bali. The study was conducted at Udayana University Hospital in July 2022. The scores used in this study were self-reported PedsQL scores and PSC-17 scores obtained based on interviews with children. The correlation between the evaluation results using the PSC-17 and PedsQL questionnaires was evaluated using the Spearman correlation test. Results : Amongst 189 children, median age was 11 years (range 11–13 years). There was a significant correlation between PSC-17 scores and PedsQL scores (r= -0.59; p<0.001). Subgroup analysis on PSC-17 aspect subscales and PedsQL dimensions found significantly varying negative correlations. Conclusion : This study found a moderate negative correlation between PSC-17 scores and PedsQL scores, varying correlations strength between each aspect/dimension of each score. Keywords: children, quality of life, PedsQL, psychosocial, PSC-17.